Analisis SWOT Sebagai Strategi Pemasaran Dalam Meningkatkan Daya Saing - Yekti Rahajeng (Ecobuss, 2022)
The objectives this research is to know how SWOT analysis as marketing strategies to improve competitiveness in CV Dua Putri Sholehah Probolinggo. This research was tested using SWOT analysis by identifying internal factors (strenghts and weaknesses) and external factors (opportunities and threats). The method used in this research in quantitative descriptive. Data collection techniques in this study were conducted by interview, observation, documentation methods and then analyzed using SWOT. The type of data consists of primary data and secondary data. The results of this research can be seen the value of internal factors of 2.99 and external factors 2,88. CV Dua Putri Sholehah Probolinggo is in quadrant II, despite facing varios threats but still has strength in terms of internal and strategies that must be applied thas is using power to take advantage of long-term opportunities and diversification strategies so that CV Dua Putri Sholehah Probolinggo can improve its competitiveness. Keyword: SWOT Analysis, marketing strategy, competitiveness